The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1016/j.spinee.2014.12.143
|View full text |Cite
|
Sign up to set email alerts
|

Functional impact of integrin α5β1 on the homeostasis of intervertebral discs: a study of mechanotransduction pathways using a novel dynamic loading organ culture system

Abstract: BACKGROUND CONTEXT Intervertebral disc (IVD) degeneration, a major cause of low back pain, is considered to be induced by daily mechanical loading. Mechanical stress is widely known to affect cell survival and extracellular matrix metabolism in many cell types. Although the involvement of integrin α5β1 transmembrane mechanoreceptor in IVD degeneration has been reported, the precise function of integrin α5β1 remains obscure. PURPOSE To reflect IVD tissue response to mechanical stress using a dynamic loading o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 48 publications
(46 reference statements)
2
32
0
Order By: Relevance
“…Integrins participate in mechanotransduction in human NP cells by acting as mechanoreceptors that detect mechanical stimulation by dynamic loading. 33 Although Tie2 is a Ang-2 receptor, it is capable of forming a complex with integrins. Numerous studies have suggested that Ang-2 exhibits context-dependent functions, eg, It acts as a vessel-destabilizing molecule in Tie2expressing ECs and as a directly pro-angiogenic molecule in Tie2-negative angiogenic ECs via integrin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Integrins participate in mechanotransduction in human NP cells by acting as mechanoreceptors that detect mechanical stimulation by dynamic loading. 33 Although Tie2 is a Ang-2 receptor, it is capable of forming a complex with integrins. Numerous studies have suggested that Ang-2 exhibits context-dependent functions, eg, It acts as a vessel-destabilizing molecule in Tie2expressing ECs and as a directly pro-angiogenic molecule in Tie2-negative angiogenic ECs via integrin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to pathway term enrichment, ECM-receptor interaction, focal adhesion, integrin and TGF- β signalling, were expected, given that most of these pathways are connected. In most of the tissues, integrin cell surface receptors mediate cell-matrix interactions, which are key to control adhesion, survival and differentiation, among others, in response to environmental cues, like mechanical stimuli 45 , 46 . Moreover, focal adhesion kinase (FAK) has been shown to be activated in response to strain in non-degenerate disc cells, in an integrin dependent manner 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin (FN) mediates a wide variety of cellular interactions with the matrix and plays important roles in cell adhesion, migration, growth, differentiation and survival, particularly through integrin interactions 4 , 46 . It interacts with a broad range of collagens (type I, II, III, IV, V and X) 49 and, in line with our results, FN has been shown to be upregulated in numerous models of disc ageing and degeneration 35 , 39 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Although one study found that physiological level of dynamic compression induced integrin α5β1 expression in rat disc explants 187 , other studies find that degenerative static compressive loading in vivo upregulate β1 expression in NP cells, and activates downstream signaling 188 .…”
Section: Cell-ecm Interactionsmentioning
confidence: 98%
“…Although one study found that physiological level of dynamic compression induced integrin α5β1 expression in rat disc explants, other studies find that degenerative static compressive loading in vivo upregulate β1 expression in NP cells, and activates downstream signaling. Moreover, disruption of β1 integrin signaling may underlie disc cell apoptosis induced by mechanical stress in disc degeneration models.…”
Section: Response To Abnormal Mechanobiology and Degenerationmentioning
confidence: 99%